Spatiotemporal patterns of connectivity and dispersal in the Adriatic Sea - Nadal Arizo, Irene; Picciulin, Marta; Falcieri, Francesco; García-Lafuente, Jesús; Sammartino, Simone; Ghezzo, Michol (My University, 2024)
Hydrodynamic features largely control the dispersal and connectivity of marine populations, especially in highly energetic areas determined by currents, river flows, and meteorological variability. Understanding how species interact with these physical processes is critical for effective management of threatened populations and identification of areas in need of conservation efforts. This study focuses on the hydrodynamics regulating connectivity in the Adriatic Sea, a shallow and semi-enclosed basin widely recognized as one of the most important areas for conservation in the Mediterranean Sea. A high-resolution hydrodynamic model coupled with a lagrangian tracking module serves as the numerical tool. Lagrangian particles in this network, representing eggs and larvae with typical biological characteristics of generic marine organisms inhabiting the region, are released throughout the basin at different times during a test year to identify the most likely pathways of individual dispersal. Presented through a traditional connectivity matrix and a novel retention clock matrix, seasonal connectivity emerges as the most influential factor, with increased variability and reduced efficiency in winter compared to summer. The duration of the pelagic larval stage is a critical factor in dispersal, as revealed by a numerical sensitivity test. The potential implications of the results for better assessment and management of highly valued marine species in the basin are highlighted.
Keywords: Hidrodinámica - Adriático; Retention Clock Matrix; Numerical modeling; Hydrodynamic connectivity